Emperipolesis – A Review - Varun Rastogi (Journal of Clinical and Diagnostic Research, 2014)
Emperipolesis is an uncommon biological process, in which a cell penetrates another living cell. Unlike in phagocytosis where the engulfed cell is killed by lysosomal enzymes of the macrophage, the cell exists as viable cell within another in emperipolesis and can exit at any time without any structural or functional abnormalities for either of them. This process can either be physiological or pathological and may be a pathognomonic feature of certain diseases. Histiocytes and Megakaryocytes are involved in Emperipolesis normally but tumour giant cells in Hodgkin’s disease and Rosai-Dorfman disease are pathologic conditions in which this process is seen. We report a mini review as this process is rare and not much reported in the literature.